What do terracotta figurines in a sacral context reveal? The case of the Aphaia sanctuary on the island of Aegina - Spathi, Maria G. (Journal of Greek Archaeology, 2022)
Figurines are one of the most numerous categories of finds, coming to light in their hundreds in sacral contexts. And while other finds, such as ceramics, fall often into the category of profane, coroplastic finds are clearly always votives. They are offerings to the deity given either singly or, possibly, in groups, along with other offerings, such as edible stuffs. The importance of figurines as votive offerings in shrines has undergone a revision: up to a few decades ago, they were considered cheap, mass-produced products of little interpretive significance to the results of modern research. Their study, when from sacred assemblages, has since progressed greatly. Many independent publications bear witness to this. Their newly-appreciated importance lies not only in their being revealing finds for the practice of worship in a place but also, when there exists, say, a repetition of types for a long time, they offer valuable information about the character, qualities, and sometimes even the very identity of the worshiped deity. And while individual figurines as votive offerings to shrines may be a personal expression of the dedicator, they all reflect a collective and repetitive practice directly related to the deity worshiped. Depending on their place of manufacture, they also provide information on domestic production, influences from other regions and the commercial relations of the sanctuaries and the wider area in which they exist with other such religious centres and other ceramic traditions. But their artistic value is not necessarily negligible. Along with the handmade or mass-produced products, there are similar coroplastic examples on a larger scale, made in multiple moulds; these may far exceed 20 cm in size. Such pieces were certainly not cheap votive offerings but expensive and perhaps made to order. In the present study, the information that may be drawn from figurines in sanctuaries is examined. The exercise takes as a case-study all the figurines from the sanctuary of Aphaia on the island of Aegina in the Saronic Gulf, which are mainly dated due to the Archaic period. This corpus is well-suited to the task in that it gives information not limited only to the typology of the figurines and their relation to the properties of the worshiped deity, but also on their origin, which goes beyond the island itself.